Sustainability Risks of Coastal Cities from Climate Change - Edward McBean; Jinhui Jeanne Huang (The Global Environmental Engineers, 2017)
Issues influencing the sustainability of coastal cities are assessed, reflecting the combination of impending sea level rise and storm surges, and increasing growth in populations in coastal cities. Geologic-time scales are utilized to draw parallels to characterize relevant historical occurrences that help to understand the context of projections of impending sea level rise issue to year 2100. Given that Antarctica holds sufficient water to raise global sea levels by 58 m if the ice were to melt, this indicates that even a small percentage of melting of the polar ice caps, should this occur, will have enormous implications to the sustainability of coastal cities which are projected to hold 12.4 percent of the world’s population by 2060. The result is the combination of predicted sea level rise and associated storm surges indicate that drastic measures must be promoted to improve the sustainability of coastal cities.